The Values of Tawhid Their Relevance to Formation of Modern Life Ethics - Latif, Abdul; Salim, Hakimuddin; Santoso, M.A. Fattah (Universitas Muhammadiyah Surakarta, 2025)
The values of monotheism in Islamic teachings play a very important role in shaping the moral and ethical foundations of a person's life. In modern life, which is full of challenges, technological developments, and rapid social changes, the application of monotheistic values is very relevant in guiding individuals to adhere to the right moral principles. This study aims to examine the relevance of tauhid values in shaping modern life ethics, emphasizing how tauhid principles can serve as a foundation for facing various moral challenges in this ever-evolving world. Through a deeper understanding of tauhid, it is hoped that each individual can integrate it into their daily lives, thereby creating a more meaningful, balanced, and responsible life. The results of this study are also expected to contribute to an understanding of how the value of tauhid can bring positive change in modern society and maintain a balance between the world and the hereafter.